2020
DOI: 10.1136/archdischild-2019-318379
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent sudden unexpected death in infancy: a case series of sibling deaths

Abstract: ObjectivesTo determine the rate of sudden unexpected death in infancy (SUDI) for infants born after a previous SUDI in the same family, and to establish the causes of death and the frequency of child protection concerns in families with recurrent SUDI.DesignObservational study using clinical case records.SettingThe UK’s Care of Next Infant (CONI) programme, which provides additional care to families who have experienced SUDI with their subsequent children.PatientsInfants registered on CONI between January 2000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Our results also agree with other studies that have shown that Non-Hispanic Black infants are at a disproportionately high SIDS risk (12,18). We also find that lower maternal education level (19), lower maternal age, male sex of the baby, and prior sibling death are associated with increased SIDS risk (20). Many of these associations have been previously shown in other studies; however, this study utilizes a more robust statistical approach, with a multivariable model, in a larger and more recent population to demonstrate FIGURE 2 | Forest plot of adjusted odds ratios for exposure to various covariates in SIDS vs. non-SIDS infants with confidence intervals.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results also agree with other studies that have shown that Non-Hispanic Black infants are at a disproportionately high SIDS risk (12,18). We also find that lower maternal education level (19), lower maternal age, male sex of the baby, and prior sibling death are associated with increased SIDS risk (20). Many of these associations have been previously shown in other studies; however, this study utilizes a more robust statistical approach, with a multivariable model, in a larger and more recent population to demonstrate FIGURE 2 | Forest plot of adjusted odds ratios for exposure to various covariates in SIDS vs. non-SIDS infants with confidence intervals.…”
Section: Discussionsupporting
confidence: 92%
“…Finally, while not statistically significant, we observed an association between SIDS and at least one of the mother's previous births now deceased. This association can be explained both by the growing literature on evidence of the role of genetic predisposition in SIDS, as well as the fact that siblings may experience similar parental child-care practices (20,33,34). To gain more insight into the heritability of SIDS on a population level, sibling and twin studies must be performed.…”
Section: Discussionmentioning
confidence: 99%
“…A positive familial aggregation study is an important step to suggest the usefulness of clinical genetic work-up of the families. Even though positive family history of SIDS has been described, 8 , 9 , 10 , 11 , 12 , 13 , 14 it is unknown whether a familial aggregation exists in the general population. Previous studies of familial aggregation were performed on small and/or selected populations 8 , 9 , 10 , 11 , 12 ; therefore, a nationwide study on an unselected pediatric population with information on family history is warranted to establish a familial clustering of children who died of SIDS.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic investigations in SUDC involve small cohorts with heterogeneous findings, yet common substrates are suggested. A hereditary contribution to SUDC is supported by the observation of recurrent cases within families and the increased risk of SIDS/SUDC in the presence of a family history of such a death 31 . In practice, clinical genetic testing most frequently relies on panels of genes associated with a common phenotype that may cause sudden death, such as epilepsy, cardiomyopathies, or cardiac arrhythmias, due to cost limitations.…”
Section: Geneticsmentioning
confidence: 99%
“…A hereditary contribution to SUDC is supported by the observation of recurrent cases within families and the increased risk of SIDS/SUDC in the presence of a family history of such a death. 31 In practice, clinical genetic testing most frequently relies on panels of genes associated with a common phenotype that may cause sudden death, such as epilepsy, cardiomyopathies, or cardiac arrhythmias, due to cost limitations. Alternatively, research groups often take a hypothesis-free approach using exome sequencing or genome sequencing, in which genome-wide sequencing is performed and analyzed for potential causal variants.…”
Section: Geneticsmentioning
confidence: 99%